The Effect of Nonverbal Cues on the Interpretation of Utterances by People with Visual Impairments. (March 2014) - Sak-Wernicka, Jolanta
Introduction: The purpose of this article is to explore the effect of nonverbal information (gestures and facial expressions) provided in real time on the interpretation of utterances by people with total blindness. Methods: The article reports on an exploratory study performed on two groups of participants with visual impairments who were tested on their ability to interpret short dialogues provided as a recording with or without audio description (AD). The AD supplied additional information about gestures and facial expressions performed by speakers in the dialogues. The performance of the visually impaired participants was compared with participants who were sighted. Results: There were no significant differences in the interpretation of the dialogues between the two groups of participants. No significant differences were found between the participants with visual impairments who were and were not provided with AD. Discussion: The findings lend support for the premise that people with visual impairments are able to make correct assumptions about intentions, feelings, and attitudes of other people on the basis of available information during communication. The results also suggest that the lack of direct access to gestures and facial expressions during communication does not tend to impair the understanding of utterances by people who are blind.